Expulsion - Pascual, Rad Paul Anthony D.S
A tight-knit friend group finally goes on a long-planned outing that takes them to various parts of their highschool life to appeal to their memory lane. Initially meeting at UP Diliman where they all study—Desi, Tala, and Sid commute to various coffee shops, lunch places, and public areas wherein they recall fond memories of their classmates and their time together. Albeit having been within the same campus, their ability and extent to remember their time becomes increasingly fuzzy as they move forwards. Tala, the shortest and cheeriest of the group, vehemently remembers every single person she's met—their face, their name, even how they talk. Desi and Sid couldn't care any less about these details, but they recall differently from each other. Misremembering classroom assignments at first, then certain details about their school's structure, and then finally their close friend.